RUMAH SUSUN SEDERHANA SEWA DAN PERKEBUNAN KOTA DI KELURAHAN PONDOK BAMBU - Giorgio Jivanka; Petrus Rudi Kasimun (Jurusan Arsitektur dan Perencanaan, 2021)
The rate of population growth in big cities, such as Jakarta, which is not followed by good quality human resources has an impact on the birth of other social problems, namely poverty. These problems can lead to conversion of agricultural land to non-agricultural land so that it has an impact on ecological changes that lead to land degradation. Rusunawa (Simple Rental Flats) is one solution to solve the problem of land degradation in urban areas. Rusunawa only solves the problem of land degradation, therefore, the presence of a program that is able to support the economic aspects of its inhabitants is also needed, such as urban plantations. On the other hand, there are social needs that residents need when changing places of residence called social adaptation. This study is intended to analyze the application of the hybrid concept in this residential project, the need for social adaptation, and determine the area of planting land needed to meet the needs of the residents of the apartment. This residential project will be guided by the hybrid concept which will be used as design criteria. The application of the hybrid concept in work-based residential buildings can be achieved through several criteria such as project scale, urban area density, function diversity, function scale, function integration, flexibility, vertical connections (that promote integration), and integrated public gathering space. Keywords: Flats; Hybrid Concept; Urban Farming; Social Adaptation AbstrakLaju pertumbuhan penduduk di kota-kota besar, seperti Jakarta yang tidak diikuti dengan kualitas SDM yang baik berdampak pada terlahirnya masalah sosial lainnya, yaitu kemiskinan. Masalah tersebut dapat menyebabkan terjadinya konversi lahan pertanian ke lahan non pertanian sehingga berdampak pada perubahan ekologis yang mengarah ke degradasi lahan. Rusunawa (Rumah Susun Sederhana Sewa) adalah salah satu solusi untuk menyelesaikan masalah degradasi lahan di perkotaan. Rusunawa hanya memecahkan masalah degradasi lahan saja, oleh karena itu, kehadiran program yang mampu menunjang aspek ekonomi penghuninya juga diperlukan, seperti perkebunan kota. Di lain sisi, terdapat kebutuhan sosial yang dibutuhkan warga saat berpindah tempat tinggal yang disebut adaptasi sosial. Kajian ini dimaksudkan untuk menganalisis penerapan konsep hybrid pada proyek hunian ini, kebutuhan atas adaptasi sosial, dan menentukan luasan lahan tanam yang dibutuhkan untuk memenuhi kebutuhan penghuni rumah susun. Proyek hunian ini akan berpedoman pada konsep hybrid yang akan dijadikan kriteria desain. Penerapan konsep hybrid pada bangunan hunian berbasis pekerjaan dapat dicapaimelalui beberapa kriteria seperti project scale, urban area density, function diversity, fuction scale, function integration, flexibility, vertical connections (that promote integration), dan integrated public gathering space.